POLA PEMAKAIAN BAHASA OLEH MAHASISWA CILACAP DI YOGYAKARTA (KAJIAN SOSIOLINGUISTIK - , LIA RESTIAWATI H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is a research that analyze the usage pattern of Cilacap students in Yogyakarta of Himpunan Mahasiswa Cilacap di Yogyakarta (HIMACITA) with applying the sociolinguistics approach theory. The researcher is interested to execute this research because there has been found in language phenomena of Cilacap students who still keep their own language even in another city. This research will describe 4 problem formulations, such as: the language usage of Cilacap students when they speak with the same Cilacap students, different and comunication partner that have higher social status, also form and code switching code of Cilacap students in Yogyakarta. This research is descriptive research. Steps that is conducted in doing this research are data collecting, data analyzing and presenting the data analysis. This research result consists of the language form of Cilacap students when they comunicate among Cilacap students, thas is a language code and code utterance level. Cilacap students, language forms when communicating with students outside Cilacap country are: (a) the way to keep BJDB, (b) following language dialect of speaking partner, (c) Cilacap students use BI (Bahasa Indonesia) to communicate, (d) language usage pattern when they communicate with students who are not from Cilacap. Language form of Cilacap students when communicating with higher level speakers that come from Cilacap with using BJ code, TTK style and Bahasa Indonesia. Later form and code swithching function of Cilacap students in Yogyakarta that included in code switching and speech level switching. Code switching function has been found in speech data including nine code switching functions.